Criterial efficiency evaluation of current conveyors - Филинюк, Николай Антонович; Лазарев, Александр Александрович; Лищинская, Людмила Брониславовна; Стахов, Владимир Петрович (Eastern-European Journal of Enterprise Technologies, 2013)
Circuit design of information devices based on current conveyors is being intensively developed at present. There are many circuits of current conveyors. Therefore there is a problem of choosing the most efficient current conveyor circuit with respect to a set of key parameters for a particular application, which can be solved by the criterion evaluation of efficiency. Analysis of current conveyor circuits efficiency has been made for the based on them design of immittance converters and circuit negatrons - devices with negative resistance, inductance, capacitance, based on results of computer simulation of three current conveyors circuits on one, two, and 18 CMOS transistors. An integrated criterion of current conveyors efficiency has been developed in the paper. Its use allows choosing the optimal conveyor circuit for a particular purpose. Among the considered current conveyors the circuit on 18 transistors is the most functional and accurate, while still having the worst frequency and power parameters. The proposed integrated criterion of efficiency evaluation with respect to a set of key parameters has shown that the circuit on a single transistor is the most efficient for the circuit negatrons design on immittance converters, because high accuracy is not so important in this case, especially for devices of immitance fuzzy logic, and the best frequency and power properties allow synthesis of high-performance information devices.